Analysis of the Knowledge, Attitude and Practice of Multiple Designers Towards Prevention-through-Design (PtD) Implementation to Malaysia’s Construction Industry - Abas, Nor Haslinda; Rusli, Nursyafiqah; Rahmat, Muhamad Hanafi (Recent Trends in Civil Engineering and Built Environment, 2021)
: Statistics as evidence reported by the Department of Occupational Safety and Health (DOSH) shows that the construction sector recorded the highest rate of deaths compared to other sectors such as manufacturing and agriculture. It is suggested that early implementation on safety and health element in the construction project by the responsible parties, or Prevention-through-Design (PtD) concept could minimize the occupational safety and health hazards and risks, and further accident. This leads to this research which aims to investigate the knowledge, attitude and practice (KAP) of multiple designers in Malaysia’s construction industry towards PtD implementation. Data was collected from multiple designers in Kuala Lumpur and Selangor using questionnaires and semi-structured interviews. The results showed that the designers’ knowledge and attitude on PtD were well-aware by the designers and the concept was well accepted. However, the practice for PtD still needs many improvements. This study is important to raise awareness about the safe design among the designers. In addition, this study also helps in investigating where Malaysia’s construction industry stands through the act of KAP of PtD by the construction stakeholders.